IMPLEMENTATION OF PROBLEM BASED LEARNING TO IMPROVE LEARNING OUTCOMES OF BODY ELECTRICAL SYSTEMS IN VOCATIONAL SCHOOLS (Universitas Pendidikan Indonesia, 2024)
This research is the application of problem-based learning to improve the study results of the body electrical system, the lighting system material is a quantitative research of the Nonequivalent control group design experiment model carried out at SMK Negeri 1 Purwakarta, this research aims to improve the study result of students reviewed from the cognitive aspect, data collection is carried out by providing pre-tests to students, then given treatment using Problem based learning, then given a post-test at the end of learning. The results showed that the study results of the experiment class showed an increase in study results in 11 students in the